Current Evidence for Spinopelvic Characteristics Influencing Total Hip Arthroplasty Dislocation Risk. Issue 8 (23rd August 2022) - van der Gronde, B.A.T.D.; Schlösser, T.P.C.; van Erp, J.H.J.; Snijders, T.E.; Castelein, R.M.; Weinans, H.; de Gast, A.
Abstract : Background: Decreased pelvic mobility and pelvic retroversion may result from spinal degeneration and lead to changes in the orientation of the acetabular implant after total hip arthroplasty (THA). While multiple patient and surgery-related factors contribute to THA dislocations, there is increasing evidence that sagittal spinopelvic dynamics are relevant for THA stability. The aim of this systematic review was to assess the relationship between previously described sagittal spinopelvic characteristics and implant dislocations after primary THA. Methods: A comprehensive literature search in the PubMed and Embase databases was conducted for studies reporting on spinopelvic morphology, alignment, pathology, or surgery and THA dislocations. Risk of bias was assessed using the MINORS criteria. Because of high heterogeneity in study methodology, a synthesis of best evidence was performed. Odds ratios (ORs), relative risks (RRs), and effect sizes (g) were calculated. Results: Fifteen studies (1, 007, 900 THAs) with quality scores of 15 to 23 out of 24 were included. Nine different spinopelvic alignment parameters (8 studies, g = 0.14 to 2.02), spinal pathology (2 studies, OR = 1.9 to 29.2), and previous spinal fusion surgery (8 studies, OR = 1.59 to 23.7, RR = 3.0) were found to be related to THA dislocation. Conflicting results were found for another sagittal pelvic morphology parameter, pelvic incidence. Conclusions: Several sagittal spinopelvic patient characteristics were found to be related to THA dislocation, and the associated risks were greater than for other patient and surgery-related factors. Future research is needed to determine which of those characteristics and parameters should be taken into account in patients undergoing primary THA. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.